Critical Heritage Studies and the Futures of Europe - Harrison, Rodney; Dias, Nélia; kristiansen, kristian (UCL Press, 2023)
Cultural and natural heritage are central to 'Europe' and 'the European project'. They were bound up in the emergence of nation-states in the eighteenth and nineteenth centuries, where they were used to justify differences over which border conflicts were fought. Later, the idea of a 'common European heritage' provided a rationale for the development of the European Union. Now, the emergence of 'new' populist nationalisms shows how the imagined past continues to play a role in cultural and social governance, while a series of interlinked social and ecological crises are changing the ways that heritage operates. New discourses and ontologies are emerging to reconfigure heritage for the circumstances of the present and the uncertainties of the future. Taking the current role of heritage in Europe as its starting point, Critical Heritage Studies and the Futures of Europe presents a number of case studies that explore key themes in this transformation. Contributors draw on a range of disciplinary perspectives to consider, variously, the role of heritage and museums in the migration and climate 'emergencies'; approaches to urban heritage conservation and practices of curating cities; digital and digitised heritage; the use of heritage as a therapeutic resource; and critical approaches to heritage and its management. Taken together, the chapters explore the multiple ontologies through which cultural and natural heritage have actively intervened in redrawing the futures of Europe and the world. Praise for Critical Heritage Studies and the Futures of Europe 'Filled with many fascinating and diverse chapters, this book vividly demonstrates the dynamism and breadth of critical heritage study of, in, and entangled with Europe today' Sharon Macdonald, Alexander von Humboldt Professor of Social Anthropology and Director of the Centre for Anthropological Research on Museums and Heritage (CARMAH) in the Institute of European Ethnology at Humboldt-Universität zu Berlin. 'Far from being restrictive, let alone chauvinistic, the multiscalar European focus of this book confirms the breadth and relevance of current critical heritage studies. With contributions addressing such topical issues as climate emergencies, urban landscapes, cultural industries, new media and identity politics - be they written by established scholars or by emerging researchers - it is ""Europe"" with all its shared grounds and recurrent divergences that comes into sharper relief. From this vantage point, readers of this compelling book will be better positioned for reflecting on and eventually influencing and challenging our heritage futures.' Nathan Schlanger, Professor of Archaeology, École nationale des chartes, Paris. 'This book addresses European heritage realities and futures through new voices, paradigms, and methods. It is a collage of tensions - practically a representation of Europe itself - through which to comprehend contemporary intersections of time, place, things, and meaning. It contributes to new vistas in heritage studies: the offer of design and imagination as methods; reckonings with data and climate change as seemingly uncontrollable actors; and the ongoing negotiation of ""criticality"" in the making of our responsibilities for the past in the present' Christopher Whitehead, Professor of Museology, Newcastle University.